Implementasi Nilai Kemanusiaan Yang Adil dan Beradab dalam Berbagai Profesi di Lingkungan Masyarakat Kota Jayapura - Marthen Timisela; Yan Tabuni (Biro Pengelolaan Penelitian dan Pengabdian Kepada Masyarat SETIA Ngabang, 2022)
There is a lack of understanding of just and civilized humanitarian values ​​in the community environment, so that the application of Pancasila values ​​​​is an obligation for Indonesian citizens as a guideline for their lives. This study discusses the implementation of just and civilized humanitarian values ​​​​in various professions in Jayapura City. By referring to previous literature reviews, this study aims to explore how these values ​​​​are internalized in daily practice in various sectors, including education, health, and government. Through qualitative methods, this study collected data from in-depth interviews and participant observations. The results show that despite the challenges, many professionals in Jayapura are committed to implementing humanitarian values ​​​​in their work, which contributes to the development of a more civilized society.